THE DISINTEGRATION OF THE SOVIET UNION. THE COLLAPSE OF BIPOLAR SYSTEM - Taisiya Igorevna Shkolyarskaya (Современная наука и инновации, 2022)
This article analizes one of the biggest failures of great-power statehood in the world history - the destruction of the existing of bipolar system of the Union of Soviet Socialist Republics. The events of national history in 19851991, the most dramatic period for the USSR, were studied